The Astronomer Jules Janssen A Globetrotter of Celestial Physics - Launay, Françoise (Astrophysics and Space Science Library, 2012)
Every aspect of the personality of Janssen (1824-1907) - that D'Artagnan of science, this bard of the Sun, and this audacious master builder - is covered here by Françoise Launay, his attentive and equally erudite biographer. A physicist, inventor and builder, Janssen was guided by his energy and curiosity. His research followed two directions: on the one hand the atmospheres of the Earth and the Sun, and on the other, two techniques: spectroscopy and photography. Among his numerous voyages across the globe, he went to Japan in 1874 to follow the transit of Venus in front of the Sun, the same year in which he invented his famous photographic revolver, which was, in truth, a great technical success. To observe the Sun during total eclipses he traveled to the Indies in 1868, to Oran in 1870 (escaping from besieged Paris by balloon!), returned to India in 1871, left for Siam in 1875 and, in 1883, for an island in the Pacific. One can thus understand why Henriette often complained of the solitude in which she was left by her peripatetic husband: "There are men who leave their wives for mistresses; you do it for journeys!" ... Basking in the glow of his success, Janssen was able to undertake the construction of the great astrophysical observatory of which he had dreamed. It was at Meudon that he had it built. From the Preface by Jean-Claude Pecker.